Prevalence and related factors of food addiction among nurses of a university hospital in Bangkok - Ngarmgan, Sita; Kalayasiri, Rasmon; Jiamjarasrangsi, Wiroj (Chulalongkorn Medical Journal, 2020)
Background: Food addiction (FA) is referred to when the need to eat becomes compulsive or uncontrollable. It may result in higher risk of various medical conditions and thus being appropriate target for designing effective therapeutic approaches for such conditions. Information about FA in Thai population is however limited nowadays. Objective: This study aimed to investigate the prevalence and related factors of FA among nurses of a university hospital in Bangkok. Methods: A cross-sectional study was conducted among 773 nurses of a university hospital in Bangkok, Thailand between April 2018 and April 2019. FA was assessed by the Thai version of the Modified Yale Food Addiction Scale Version 2.0 (mYFAS 2.0). Associations of personal demographics and various potential risk factors with FA were examined by logistic regression analyses and the odds ratio (OR) as measures of association. Results: The prevalence (95% confidence interval or CI) of FA was 9.7% (7.6 - 11.8). The proportions of mild, moderate and severe FA of 48.0%, 26.7% and 25.3%, respectively. Factors which were significantly and independently associated with FA included the presence of medical condition (OR = 2.55; 95%CI = 1.16 - 5.62), doing part-time job (OR = 3.86; 95%CI = 1.68 - 8.88), low decision latitude on working (OR =2.49; 95%CI = 1.37 - 4.52), and higher number of buffet per month (OR = 2.27, 2.85, and 2.51 respectively for having 1 - 2, 3 - 4, and more than 4 buffets per month). In addition, having couple and colleague as the influencer of eating habit (OR = 4.87 and 2.24 respectively) and the presence of chronic pain and depress as the stress symptoms (OR = 2.96; 95%CI = 1.10 - 7.92) also associated with FA. Conclusions: FA prevalence among nurses in this university hospital was quite high. A number of factors related to personal health, work, and eating were significantly associated with FA. Additional longitudinal studies are imperative before being firmly conclude about the causality of such associations.